EKSTRAKSI DAN OPTIMASI VITAMIN E DARI FRAKSI NON POLAR CRUDE PALM OIL (CPO) - Hilma, Rahmiwati; Anggita, Anggi Fisi; Ikhtiarudin, Ihsan (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2018)
Vitamin E has many benefits for human health. Besides being known as supplements, vitamin E is known to have activities as an anticancer compound, preventing premature aging, preventing cardiovascular diseases and other degenerative diseases. In this study carried out the extraction and optimization process of vitamin E from sample non-polar fraction of fresh CPO. The extraction process was carried out by saponification reaction, vitamin E optimization was carried out on the non-polar fraction with the addition of methanol, then to the oil fraction added 2-propanol (1%) in hexane. From the fresh CPO samples used, it was seen that the samples met the quality standards of fresh CPO. From the results of extraction and optimization of vitamin E, it was found that the yield was quite large (52.77%). Characterization results with TLC and analyzed with UV light at a wavelength of 254 and 366 nm seen vitamin E still has 2 stains, the possibility was tocopherol and tootrienol which was usually components contained in vitamin E.